2014
DOI: 10.1039/c4cc01722f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multi-substituted vinylsilanes via copper(i)-catalyzed hydrosilylation reactions of allenes and propiolate derivatives with silylboronates

Abstract: An efficient and general copper(I)-catalyzed method for the synthesis of multi-substituted vinylsilanes is reported. Multi-substituted allenes with electron-withdrawing groups and propiolate derivatives reacted well with (dimethylphenylsilyl)boronic acid pinacol ester to afford silyl-substituted butenoate derivatives and β-silyl-substituted acrylate derivatives, respectively. The corresponding products could be obtained in moderate to high yields and with good to excellent stereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Finally,apreliminary study illustrates that the threecomponent approach to functionalized homoallylic amines can be extended to the silylative cross-coupling of allenes and imines. [18] Employing Suginomes reagent, Me 2 PhSiBpin, [19] in arelated copper-catalyzed assembly involving 1a and 2a gave the homoallylic amine 3x with complete regiocontrol, high diastereocontrol, and in good yield (Scheme 8).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Finally,apreliminary study illustrates that the threecomponent approach to functionalized homoallylic amines can be extended to the silylative cross-coupling of allenes and imines. [18] Employing Suginomes reagent, Me 2 PhSiBpin, [19] in arelated copper-catalyzed assembly involving 1a and 2a gave the homoallylic amine 3x with complete regiocontrol, high diastereocontrol, and in good yield (Scheme 8).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…It was reported that Cu–Si species could react with allenes to form β‐silylated allylcopper intermediates 14. 15 Their three subsequent transformations were reported using different electrophiles: MeOH for hydrosilylation,14a,b aldehydes and ketones for 1,2‐addition,14a,c and CO 2 for silacarboxylation 15. Despite these advances, the challenging 1,4‐addition of β‐silylated allylcopper has never been uncovered, because efficient 1,2‐addtion remains favored versus 1,4‐addition in the addition of β‐functionalized allylcopper to α,β‐unsaturated carbonyls (Scheme ) 16.…”
Section: Methodsmentioning
confidence: 99%
“…These reactions tended to have high yields and high regioselectivity (Table ). Notably, two of these methods can be performed in water (Methods A and B) . Furthermore, Xu showed that silylation of an enynoate can proceed with exclusive addition to the β-carbon rather than the δ-carbon …”
Section: Silylations Using Silylboranesmentioning
confidence: 99%